Toxoplasma gondii and Giardia duodenalis infections in domestic dogs in New York City public parks. (May 2016) - Munoz, Jonathan; Mayer, D.C. Ghislaine
Highlights: Molecular diagnostic tools were used to determine prevalence and genotypes of T. gondii and G. duodenalis in domestic dogs frequenting public parks in New York City, USA. A prevalence of 3.4 % for T. gondii and 15% for G. duodenalis, respectively, was detected. Zoonotic assemblage A of G. duodenalis was dominant. Further studies are necessary to establish infection dynamics. Abstract: Toxoplasma gondii and Giardia duodenalis have been widely reported to produce major diseases in humans and domestic animals. Little is known about the occurrence of these protozoan parasites in domestic dogs in the United States. The goal of this study was to determine the prevalence and genotypes of T. gondii and G. duodenalis among dogs in New York City. Fecal samples from domestic dogs were analyzed by polymerase chain reaction (PCR). Overall, 3% of the samples tested positive for T. gondii, while 15% were positive for G. duodenalis . PCR-RFLP of T. gondii -positive samples revealed genotypes I and III, while sequence analysis of the G. duodenalis -positive samples indicated that 94.1% of the dogs were infected with the zoonotic assemblage A. Further studies are needed to determine the prevalence of zoonotic protozoan parasites in domestic dogs.